A Simulation Study to Evaluate Constraints for Nonlinearity Parameter Estimation Using the Depletion Method - Romero, A.; Lavarello Montero, R.; Coila, A. (Institute of Electrical and Electronics Engineers, 2023)
The acoustic nonlinearity parameter (B/A) can assess changes in structure and identify tissue characteristics. Its accurate estimation is critical for correct ultrasound imaging and diagnosis, particularly in liver diseases. Recently, a pulseecho B/A estimation method has been developed based on the quantification of a term called the depletion of the fundamental band, using a dual-energy approach and a reference phantom. This method is accurate even though the medium and reference phantom have different attenuation coefficients. Through a methodology based on computer simulations of sample and reference phantom media, this study aims to identify constraints in the estimation of the B/A using the depletion method to measure the influence of factors such as the low excitation pressure, the scaling factor between low and high pressures, and the attenuation mismatch between reference phantom media and sample. The use of computer models of pulse-echo ultrasound provided a controlled environment to investigate the impact of these variables on the B/A estimation process. The results show that cases using moderate scaling factors (5-10) and moderate initial pressures (40-400 kPa) resulted in mean and standard deviation percentage error values usually below 10%, even in the case of 33% attenuation mismatch. Clinical Relevance—Non-alcoholic fatty liver disease (NAFLD) is a type of steatosis that affects individuals who consume little or no alcohol. The overall prevalence of NAFLD worldwide was estimated to be 32.4%. An innovative approach for NAFLD early diagnosis is the use of the B/A that can be addressed with a better understanding of constraints of the recently proposed depletion method
Keywords: Acoustic nonlinearity parameter; B/A estimation; Liver steatosis; https://purl.org/pe-repo/ocde/ford#3.02.02